Magnolia officinalis enhanced immune responses and the resistance to Vibrio harveyi infection in pearl gentian groupers - Zhang, Yilin; Li, Yuhao; Xu, Xinlan; Xu, Luxi; Li, Weifu; Gan, Zhen; Lu, Yishan (Frontiers in Veterinary Science, 2025)
Magnolia officinalis (MO) is a kind of traditional Chinese herbs, which has been studied for thousands of years in Chinese pharmacopoeia. In recent years, MO has been reported as an antibacterial agent in aquaculture, but the antibacterial properties of MO against Vibrio harveyi infection in fish remains unexplored. In this study, the effects of MO treatment on immune responses and the resistance to V. harveyi infection were detected in pearl gentian groupers. The results revealed that the expression levels of immune-related genes (IL-12, TLR2, TLR5S, CD4, MHC-Iα, and IFN-γ) in spleen, head kidney, liver and thymus, and the enzyme activities of CAT, SOD, LZM, and total serum protein in serum were significantly up-regulated at most of time points in MO -treated groupers. After being challenged with V. harveyi ZJ0603 at 28 days post-injection, the survival rate (SR) of groupers were 50.0, 60.0, 73.3, and 66.7% in MO groups at different concentrations, respectively, indicating that MO administration could improve the resistance to V. harveyi infection in groupers. The present study revealed that MO can be considered as a promising immunostimulant to induce the immune responses against V. harveyi infection in marine fishes.